Role of SHIP-1 in the adaptive immune responses to aeroallergen in the airway - Sukit Roongapinun (2018)
Background: Th2-dominated inflammatory response in the airway is an integral component in the pathogenesis of allergic asthma. Accumulating evidence supports the notion that the phosphoinositide 3-kinase (PI3K) pathway is involved in the process. We previously reported that SHIP-1, a negative regulator of the PI3K pathway, is essential in maintaining lung immunohomeostasis, potentially through regulation of innate immune cells. However, the function of SHIP-1 in adaptive immune response in the lung has not been defined. We sought to determine the role of SHIP-1 in adaptive immunity in response to aeroallergen stimulation in the airway. Methodology/Principal Findings: SHIP-1 knockout (SHIP-1-/-) mice on BALB/c background were immunized with ovalbumin (OVA) plus aluminum hydroxide, a strong Th2-inducing immunization, and challenged with OVA. Airway and lung inflammation, immunoglobulin response, Th2 cytokine production and lymphocyte response were analyzed and compared with wild type mice. Even though there was mild spontaneous inflammation in the lung at baseline, SHIP-1-/-mice showed altered responses, including less cell infiltration around the airways but more in the parenchyma, less mucus production, decreased Th2 cytokine production, and diminished serum OVA-specific IgE, IgG1, but not IgG2a. Naidotless̈ve and OVA sensitized SHIP-1-/-T cells produced a lower amount of IL-4. In vitro differentiated SHIP-1-/-Th2 cells produced less IL-4 compared to wild type Th2 cells upon T cell receptor stimulation. Conclusions/Significance: These findings indicate that, in contrast to its role as a negative regulator in the innate immune cells, SHIP-1 acts as a positive regulator in Th2 cells in the adaptive immune response to aeroallergen. Thus any potential manipulation of SHIP-1 activity should be adjusted according to the specific immune response. © 2010 Roongapinun et al.